Impaired Isometric, Concentric, and Eccentric Rate of Torque Development at the Hip and Knee in Patellofemoral Pain - Ferreira, Amanda S.; de Oliveira Silva, Danilo; Barton, Christian J.; Briani, Ronaldo V.; Taborda, Bianca; Pazzinatto, Marcella F.; de Azevedo, Fábio M (Wolters Kluwer, 2021)
ABSTRACT: Ferreira, AS, de Oliveira Silva, D, Barton, CJ, Briani, RV, Taborda, B, Pazzinatto, MF, and de Azevedo, FM. Impaired isometric, concentric, and eccentric rate of torque development at the hip and knee in patellofemoral pain. J Strength Cond Res 35(9): 2492-2497, 2021-The aims of this study were to compare maximal muscle strength and rate of torque development (RTD) of knee extensor and hip abductor during isometric, concentric, and eccentric contractions between women with and without patellofemoral pain (PFP). Thirty-eight women with PFP (PFPG) and 38 pain-free women (CG) participated in this study. Isometric, concentric, and eccentric maximal torque and RTD of knee extensor and hip abductor were assessed using an isokinetic dynamometer. Rate of torque development was calculated as the change in torque over the change in time from torque onset to 30, 60, and 90% of the maximal torque (RTD30%, RTD60%, and RTD90%) during isometric, concentric, and eccentric contractions. PFPG had lower isometric, concentric, and eccentric knee extensor maximal torque (29.9, 28.3, and 26.7%) compared with the CG. For knee extensor RTD, PFPG had slower isometric RTD30% (17.8%), RTD60% (21.5%), and RTD90% (23.4%); slower concentric RTD30% (35.7%), RTD60% (29.3%), and RTD90% (28.2%); and slower eccentric RTD30% (20.5%), RTD60% (25.2%), and RTD90% (22.5%) compared with the CG. PFPG had lower isometric, concentric, and eccentric hip abductor maximal torque (28.3, 21.8, and 17%) compared with the CG. For hip abductor RTD, PFPG had slower isometric RTD30% (32.6%), RTD60% (31.1%), and RTD90% (25.4%); slower concentric RTD90% (11.5%); and slower eccentric RTD30% (19.8%), RTD60% (26.4%), and RTD90% (24%) compared with the CG. In conclusion, women with PFP presented deficits in both maximal strength and RTD of knee extensor and hip abductor during isometric, concentric, and eccentric contractions, which highlight the potential importance of addressing different aspects of muscle function through exercise therapy.